Cluster analysis to explore morphological variation of banana (Musa spp.): A case study in Jember and Lumajang, East Java, Indonesia - Sa'diyah, Halimatus; Sari, Vega Kartika; Rusdiana, Riza Yuli; Khofi, Achmad Chaqiqotul (Kultivasi, 2025)
Banana (Musa spp.) is an important horticultural plant with a high variety in Indonesia; yet, knowledge on the morphological characteristics of indigenous bananas in East Java remains inadequate. This research aims to identify the variation and classify banana cultivars in East Java based on morphological character. The exploration was conducted using the accidental sampling method. The observations include 15 qualitative and 9 quantitative characters. Descriptive statistics were used to evaluate the data, followed by cluster analysis using the average linkage method and Euclidean distance. The exploration resulted in 15 banana cultivars with varying morphology. The cluster analysis shows banana cultivars can be divided into four major groups. The first group includes six banana cultivars distinguished by many hands per bunch and a short petiole length. The second group comprises seven banana cultivars with medium leaf length and stem diameter, with Morosebo and Musang being the outliers. The third and fourth groups have only one banana cultivar, Musang and Agung, respectively. The Musang banana has distinct physical characters, most notably a large stem diameter, whilst the Agung banana has a longer fruit length and wider fruit circumference than others. The coefficient of variation (CV) is moderate, with the fruit length, fruit circumference, fruit stem diameter, and stem diameter all having a CV greater than 47%. Thus, they have the potential for further development through plant breeding programs